Performance analysis and temperature field study of IPMSM for electric vehicles based on winding transformation strategy - Xu, Xuefeng; Zhang, Guoqiang; Li, Guangkuo; Zhang, Bingyi (IET electric power applications, 2020)
Recently, the high-performance and high-reliability permanent-magnet synchronous machine (PMSM) has attached intensive attention due to development of electric vehicles (EVs). In this study, in order to improve the capability of output torque, an improved method of interior PMSM (IPMSM) for EV based on winding transformation (WT) strategy is proposed. In the proposed method, the power electronics technology, the vector control algorithm, and the multiple-field analysis including electromagnetic field, fluid field, and temperature field are combined. Therefore, the steady-state and dynamic performances of WT-IPMSM are analysed comprehensively. The accuracy of the temperature field calculation is improved by the electromagnetic–thermal iterative method. Meanwhile, the influence of pulse-width modulation time harmonics caused by inverter on the eddy current loss of PMs and related laws is summarised. Finally, the effectiveness and feasibility of the proposed method is verified by the prototype test.